Question and Answer Service Reviewed - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
The mandate of CTA is to diffuse information, which it has been doing in a variety of ways ever since it was established. In this interview with Thiendou Niang, Documentation Chief, we learn more about the role that the Question and Answer Service...